Función sexual en pacientes con hiperplasia benigna de próstata sometidos a resección transuretral de próstata - Fernández Villacorta, Freddy Javier (2003)
The purpose of the study was to evaluate if transurethral resection of the prostate affects sexual function. Also evaluate the degree of erectile dysfunction that occurs in the same patients undergoing surgery. The sexual function of 59 patients diagnosed with benign prostatic hyperplasia before and after transurethral resection of the prostate was evaluated using the International Index of Erectile Function (IIEF) in Hopsital Víctor Larco Echegaray of Trujillo, in fourteen months that the work lasted. It was found that the average age was 63.05 years with a range of 48-84 years. HT and hypercholesterolemia were the most common associated diseases. There were no statistical differences when evaluating erectile function. 83.1% presented a mild-bruised degree of erectile dysfunction prior to TURP. So it concludes the following: 1. Transurethral resection of the prostate does not affect the sexual function of patients with benign prostatic hyperplasia. 2. Patients undergoing transurethral resection of the prostate due to benign prostatic hyperplasia presented a mild-moderate degree of ED (83.1%)